Urgency of reforming the zakat management system in Indonesia - Su’udi, Muhammad Arif; Kusnadi, Egi Hadi; Rouf, Abd. (LP3M Universitas Islam Zainul Hasan Genggong, 2025)
BAZNAS is an institution authorized to manage zakat nationally. In terms of calculating the percentage of zakat according to the law, it is not the main task of BAZNAS, but is left to the muzakki themselves. This is contrary to the spirit in the concept of zakat itself (khudh min amwalihim sadaqah). Among the impacts of the ineffectiveness of the system that is most felt is the distance between the potential and the amount of zakat that BAZNAS has managed to collect. The potential for zakat in Indonesia reaches 327 trillion per year, while the acquisition of zakat in 2023 is only 20 trillion. This research is a normative legal research with a conceptual-descriptive approach and use the legal content analysis technique. The theoretical framework used in this study is the concept of the spirit of zakat management and the concept of zakat as a public financial instrument. The conclusion obtained from this study is the need for system reform through strengthening the position and more attention by the state to BAZNAS as a trusted institution in the eyes of Muslims, so that it can be relied on to be used as part of public revenue institutions. In addition, BAZNAS also needs to change the perspective that zakat is an initiative of muzakki to pay it, but must be more active in